2018
DOI: 10.3390/ph11040097
|View full text |Cite
|
Sign up to set email alerts
|

Sucrosomial® Iron: A New Generation Iron for Improving Oral Supplementation

Abstract: Iron deficiency (ID) is usually treated with oral iron salts, but up to 50% of patients complain of gastrointestinal side effects, leading to reduced compliance with treatment. Intravenous (IV) iron formulations are increasingly safe, but there is still a risk of infusion, hypersensitivity reactions and the need for venous access and infusion monitoring. Sucrosomial® Iron (SI) is an innovative oral iron formulation in which ferric pyrophosphate is protected by a phospholipid bilayer plus a sucrester matrix (su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
108
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 80 publications
5
108
0
1
Order By: Relevance
“…Our cost minimization analysis is based on the main clinical trial result, that is the demonstrated same efficacy of oral iron and IV iron. Sucrosomial iron has demonstrated a similar effectiveness, with lower costs, in patients usually receiving IV iron (e.g., chronic kidney disease, cancer, bariatric surgery) in several studies published recently [25][26][27][28]. In particular, Darbà et al [26] conducted a budget impact analysis of an oral sucrosomial iron in the treatment of patients similar with those of our study.…”
Section: Discussionsupporting
confidence: 82%
“…Our cost minimization analysis is based on the main clinical trial result, that is the demonstrated same efficacy of oral iron and IV iron. Sucrosomial iron has demonstrated a similar effectiveness, with lower costs, in patients usually receiving IV iron (e.g., chronic kidney disease, cancer, bariatric surgery) in several studies published recently [25][26][27][28]. In particular, Darbà et al [26] conducted a budget impact analysis of an oral sucrosomial iron in the treatment of patients similar with those of our study.…”
Section: Discussionsupporting
confidence: 82%
“…(Supplementary Table S1). This result is consistent with previous studies indicating low toxicity SFP [24,53,54].…”
Section: The Effect Of Oral Iron Supplementation On Placental Morpholsupporting
confidence: 94%
“…( Supplementary Figure 1). This result is consistent with previous studies indicating low toxicity SFP [24,53,54]. To check the potential effect of SFP on the integrity and morphology of placenta we performed an exhaustive analysis of placenta using scanning electron microscopy at different scanning resolutions.…”
Section: The Effect Of Oral Iron Supplementation On Placental Morpholsupporting
confidence: 90%
“…However, the estimated absorption rate of ferrous salts is 10-15% [33]. Sucrosomial ® iron, a newer iron formulation in which ferric pyrophosphate is protected by a phospholipid bilayer and sucrosome, has been shown to be better tolerated than oral iron salts and has demonstrated high iron bioavailability [34]. Korcock et al (2018) [23] reported using Sucrosomial ® iron and was the only study that found an increase in serum iron between the probiotic and control groups.…”
Section: Discussionmentioning
confidence: 99%